Selective HIV-1-induced downmodulation of CD4 and coreceptors. - Chenine, A; Sattentau, Q; Moulard, M (2000)
CD4 and members of the chemokine receptor family are required for infection of host cells, in vitro and in vivo, by the human immunodeficiency virus type-1. Although it is established that HIV-1 gp 120 interacts with CD4 and the coreceptors CCR5 or CXCR4 at the plasma membrane during HIV entry, longer-term interactions taking place between these molecules and HIV Env are less well understood. We have measured the cell surface expression of CD4, CCR5 and CXCR4 on a CD4+/CXCR4+CCR5+ T cell line following infection by cell line-adapted X4 and primary X4, X4R5 and R5 viruses. We report a selective downmodulation of CD4 by X4 and R5X4 viruses, but not by R5 viruses. None of the viruses tested significantly reduced CXCR4 expression at any time after infection. CCR5 protein and mRNA expression was eliminated by chronic infection with R5 viruses. These results indicate that chronic HIV-1 infection has distinct effects on CD4 and coreceptor membrane expression that depends on viral origin and coreceptor usage.